Using the PEPPA framework to develop the nurse practitioner role in emergency care: Critical reflections. (September 2022) - Boman, Erika; Gaarde, Kim; Levy-Malmberg, Rika; Wong, Frances Kam Yuet; Fagerström, Lisbeth
In this article, we describe and critically reflect on how the PEPPA framework, aP articipatoryE vidence-basedP atient-focusedP rocess forA dvanced Practice Nursing, was used to develop a new model of care including the nurse practitioner (NP) role in an emergency department in Norway, where the role is in its infancy. While there is limited earlier research on the applicability of the PEPPA framework, it was here found to be useful. Supported by the framework, we mapped the current model of care, identified stakeholders and participants, determined the need for a new model of care, identified priority problems and goals, and defined the new model of care and the NP role. The PEPPA framework is recommended to develop new models of care including the NP role. Nonetheless, the process has not been straightforward. It is noted that to communicate and establish the new role in a setting as demanding as an emergency department takes time. Support from the management team is essential to succeed in developing and establishing new models of care and new nursing roles, such as the nurse practitioner role.